2011
DOI: 10.4310/ajm.2011.v15.n4.a4
|View full text |Cite
|
Sign up to set email alerts
|

Extend Mean Curvature Flow with Finite Integral Curvature

Abstract: In this note, we first prove that the solution of mean curvature flow on a finite time interval [0, T ) can be extended over time T if the space-time integration of the norm of the second fundamental form is finite. Secondly, we prove that the solution of certain mean curvature flow on a finite time interval [0, T ) can be extended over time T if the space-time integration of the mean curvature is finite. Moreover, weshow that these conditions are optimal in some sense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…Note that the constant in Theorem 1.7 does not depend on the initial hypersurface, but only on a dimension. Finally, up to a constant depending on the dimension n and the initial hypersurface M 0 , our estimate (1.9) is implied as well by the estimate (27) in Theorem 14 of [15]. This can be seen using Hölder's inequality and volume bound during the mean curvature flow as in Lemma 1.4 in Ecker [8].…”
Section: Remark 12mentioning
confidence: 83%
See 1 more Smart Citation
“…Note that the constant in Theorem 1.7 does not depend on the initial hypersurface, but only on a dimension. Finally, up to a constant depending on the dimension n and the initial hypersurface M 0 , our estimate (1.9) is implied as well by the estimate (27) in Theorem 14 of [15]. This can be seen using Hölder's inequality and volume bound during the mean curvature flow as in Lemma 1.4 in Ecker [8].…”
Section: Remark 12mentioning
confidence: 83%
“…The precise estimate of the form (1.9) for the case of minimal submanifolds can be found in Shen-Zhu [20], Proposition 2.2 (see also [4]). Moreover, in [18,27,28], the authors showed that if the L n+2 norm in space-time of the second fundamental form (or the mean curvature but under various convexity assumptions) is finite then it is possible to extend the mean curvature flow beyond the time interval under consideration. Our theorem can be viewed as a local version of these results without imposing any convexity assumptions.…”
Section: Remark 12mentioning
confidence: 98%
“…In [21] B. Wang proved that if For the mean curvature flow, the same extension problem has also been studied. The supremum and certain scaling invariant space-time integrals of the norm of the second fundamental form are known to blow up at a finite singular time ( [11], [17], [18], [24]). Moreover, the surprising fact that a subcritical integral quantity has to blow up was proved by N. Le in [12]: Theorem 1.5 (N.Le).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Le-Šešum [12] and Xu-Ye-Zhao [25] obtained some integral conditions to extend the mean curvature flow of hypersurfaces in the Euclidean space independently. Later, Xu-Ye-Zhao [26] generalized these extension theorems to the case where the ambient space is a Riemannian manifold with bounded geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Let A and H be the second fundamental form and the mean curvature vector of M , respectively. In this paper, we first generalize the extension theorems in [12,25,26] to the mean curvature flow of submanifolds in a Riemannian manifold with bounded geometry. LetÅ be the tracefree second fundamental form, which is defined byÅ = A − 1 n g ⊗ H. Denote by || · || p the L p -norm of a function or a tensor field.…”
Section: Introductionmentioning
confidence: 99%